Valve Ultrastructure and Description of a new Luticola D.G.Mann (Bacillariophyceae) species from Colorado, USA - Shea, Rachel; Greifenstein, Jeremy; Kociolek, J.p. (Phytotaxa, 2022)
A new species of the diatom genus Luticola D.G.Mann is described from a wet meadow environment from Gunnison County, Colorado, based on light and scanning electron microscopy. The new species has rugose valves, with longitudinal interruptions in the striae. Unlike other species of the genus, L. coloradiana sp. nov. has a simple structure of the internal stigma, lacking the complex opening seen in all other species in the genus. The new species resembles L. plausibilis (Hustedt) D.G.Mann, described from Franz Josef Land in the Arctic, but differs in valve shape and density of the striae. Luticola coloradiana sp. nov. also resembles L. plausibiloides Metzeltin et al., a species described from subtropical Uruguay, but differs in striae density and the rugose nature of the valves. Further research is needed to assess if the similar species from the Arctic and subtropical South America also possess the unique stigma structure seen in L. coloradiana sp. nov.